"WE HAVE CODE WORDS FOR EVERYTHING": MAINTENANCE STRATEGIES OF WOMEN IN SAME-SEX RELATIONSHIPS IN KADUNA METROPOLIS, NORTH-WEST NIGERIA - Abdullahhi, Sani; Mohammed Muazu, Ahmed; Abdulqadir, Jaafar (African Journal of Social and Behavioural Sciences, 2026)
This study examines maintenance strategies among women in same-sex relationships in Kaduna Metropolis, North-Western Nigeria, a context shaped by religious values, legal prohibition under the Same-Sex Marriage (Prohibition) Act 2014, and strict gender expectations. Guided by symbolic interactionist theory, the qualitative study employed in-depth interviews with 22 women in same-sex relationships across four Local Government Areas, plus ten key informant interviews with community and religious leaders and civil society actors. Thematic analysis revealed five maintenance strategies: coded communication systems (private languages, pet names, and nonverbal cues); spatial and temporal management through orchestrated schedules; financial interdependence via informal savings schemes (esusu/ajo) and joint business ventures; selective disclosure to trusted allies; and spiritual reframing that situates relationships within concepts of divine love and destiny. The study concludes these strategies represent adaptive responses through which women sustain intimate partnerships despite structural constraints, contributing to understanding relationship maintenance under legal and social prohibition